Ep-CAM expression in pancreatic and ampullary carcinomas: frequency and prognostic relevance. Issue 1 (14th June 2006) - Fong, D; Steurer, M; Obrist, P; Barbieri, V; Margreiter, R; Amberger, A; Laimer, K; Gastl, G; Tzankov, A; Spizzo, G
Abstract : Aims: Pancreatic adenocarcinoma is an aggressive gastrointestinal malignancy with only a few long-term survivors even after radical surgery. Patients with ampullary cancer have a better prognosis but adjuvant therapy needs further improvement. Epithelial cell adhesion molecule (Ep-CAM) is strongly expressed in a variety of epithelial cancers and represents a promising target for immunological tumour therapy. Thus, the aim of this study was to investigate Ep-CAM expression and its potential prognostic impact in pancreatic and ampullary carcinomas. Methods: Ep-CAM expression was investigated retrospectively by immunohistochemistry in paraffin-embedded primary tumour tissue samples from a series of consecutive patients with pancreatic (n = 153) and ampullary cancer (n = 34). Results: Ep-CAM overexpression was observed in 85 of 153 pancreatic cancer specimens (56%) and in 29 of 34 ampullary cancer samples (85%). Overall, Ep-CAM failed to be an independent prognostic marker. However, subgroup analyses showed that Ep-CAM overexpression correlated with shorter overall survival among patients with ampullary cancer and advanced stage pancreatic cancer. In the latter subgroup, survival gradually worsened with increasing Ep-CAM scores. Furthermore, in ampullary cancer, Ep-CAM overexpression was found to correlate with tumour stage. Conclusions: Ep-CAM overexpression was detectable in the majority of cases with pancreatic and ampullary cancer. Therefore, Ep-CAM represents an attractive target for immune-based therapeutic interventions in these tumour entities. However, the prognostic value of Ep-CAM overexpression remains undetermined.